Selective EGFR (Epidermal Growth Factor Receptor) Deletion in Myeloid Cells Limits Atherosclerosis—Brief Report. Issue 1 (January 2018) - Zeboudj, Lynda; Giraud, Andréas; Guyonnet, Lea; Zhang, Yujiao; Laurans, Ludivine; Esposito, Bruno; Vilar, Jose; Chipont, Anna; Papac-Milicevic, Nikolina; Binder, Christoph J.; Tedgui, Alain; Mallat, Ziad; et al.
Abstract : Objective—: To determine the consequences of specific inhibition of EGFR (epidermal growth factor receptor) in myeloid cells in atherosclerosis development. Approach and Results—: Atherosclerotic lesion size was significantly reduced in irradiated Ldlr −/− mice reconstituted with LysM Cre+ Egfr lox/lox bone marrow, compared with chimeric Ldlr −/− mice reconstituted with LysM Cre− Egfr lox/lox bone marrow, after 4 (−43%; P <0.05), 7 (−34%; P <0.05), and 12 weeks (−54%; P <0.001) of high-fat diet. Reduction of lesion size was associated with marked reduction in macrophage accumulation and necrotic core size. Specific deletion of Egfr in myeloid cells reduced TNF-α (tumor necrosis factor-α) and IL (interleukin)-6 production by stimulated macrophages but had no effect on IL-10 and IL-12p70 secretion. Finally, we found that myeloid deletion of Egfr limited cytoskeletal rearrangements and also lipid uptake by macrophages through a downregulation of the scavenger receptor CD36 (cluster of differentiation 36). Conclusions—: Gene deletion of Egfr in myeloid cells limits IL-6 and TNF-α production, lipid uptake, and consecutively reduces atherosclerosis development. Abstract : Supplemental Digital Content is available in the text.